ABB TOURISM FRAMING IN IDENTIFYING TOURISM POTENTIAL IN TANAKEKE ISLANDS, TAKALAR REGENCY - Nasrullah - Nasrullah; Syamsul Alam Paturusi; I Made Adikampana; I Putu Anom (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
This research aims to identify the tourism potential of the islands in Tanakeke, Takalar Regency which is located in the southern part of South Sulawesi with the framing of Natural, Cultural and Artificial (ABB) tourism. The research method used was qualitative with a descriptive approach. The research was conducted by means of: observation, interviews, and documentation. The results showed that there were 3 (three) indicators of tourism potential identification including: (1) Identification of natural tourism potential (beaches, seas, lakes, fisheries, ponds, seagrass beds, mangrove forests, plantations / fields, farms, coral reefs, and seaweed). Various types of natural tourism potential that exist and are scattered in almost all areas of the Tanakeke islands are a great potential as a basis for the development of various types of tourism activities both natural tourism, water tourism, educational tourism, agro-tourism to sports tourism; (2) Identification of cultural tourism potential (arts, traditions, crafts, livelihoods, culinary, cultural festivals, historic buildings / buildings, historical relics, traditional equipment & technology systems, and other cultural elements). Various types of cultural tourism potential that exist and are scattered in almost all areas of the Tanakeke islands are a great potential as a basis for the development of various types of tourism activities both historical tourism, cultural tourism, culinary, to events and festivals; (3) Identification of artificial tourism potential of all things created by humans by utilizing the potential of nature or the surrounding environment, for the purpose of recreation and entertainment as well as adding to the travel experience. After identifying tourism potential properly through ABB tourism framing, this can be used as a basis for managing and developing various types of tourism. In terms of management, coordination should be carried out with various parties and related stakeholders to provide basic knowledge about tourism for all villagers on the Tanakeke islands which can then be followed up by providing further action in the form of assistance by providing education, training, skills development for villagers.